The needs of women who have experienced “maternal near miss“: A systematic review of literature - Sedigheh Abdollahpour; Abbas Heydari; Hosein Ebrahimipour; Farhad Faridhosseini; Talat Khadivzadeh (Iranian Journal of Nursing and Midwifery Research, 2019)
Background: Maternal Near Miss (MNM) event is associated with emotional, psychological, and social effects on women. Determining the needs of women with these experiences is the key to programming for providing high-quality care and reducing its burden. Hence, this study was conducted to determine the needs of women who have experienced MNM. Materials and Methods: In this literature systematic review, to achieve the intended information, articles published in Web of Science and PubMed databases were systematically searched. The search strategy focused on three keywords or phrases: “maternal morbidity“ OR “maternal near miss“ AND “needs.“ Publication date was all relevant articles before 2019, and publication language was restricted to English. Article search was conducted by two independent reviewers. After the primary search, 2140 articles were found. Eventually, 77 articles, including 20 qualitative studies and 57 quantitative studies, were enrolled for final evaluation. Results: According to the results, the needs of these women could be categorized into six groups of “Management and care needs of health system,“ “Educational needs of health system,“ “Follow up and continuity of care at the primary care level,“ “Need to develop a physical, psychological and social of care packages,“ “Social support,“ and “Psychosocial support and counseling.“ Conclusions: The near-miss events change the mothers' living conditions, and therefore, they need to receive special support, given the difficult conditions they are undergoing. It is necessary that a supportive program be designed to follow-up MNM after the discharge to be run by the primary care team.